Robustness of Nutrient Signaling Is Maintained by Interconnectivity Between Signal Transduction Pathways - Welkenhuysen, Niek; Schnitzer, Barbara; Österberg, Linnea; Cvijovic, Marija (Frontiers in Physiology, 2019)
Systems biology approaches provide means to study the interplay between biological processes leading to the mechanistic understanding of the properties of complex biological systems. Here, we developed a vector format rule-based Boolean logic model of the yeast S. cerevisiae cAMP-PKA, Snf1 and the Snf3-Rgt2 pathway to better understand the role of crosstalk on network robustness and function. We identified that phosphatases are the common unknown components of the network and that crosstalk from the cAMP-PKA pathway to other pathways plays a critical role in nutrient sensing events. The model was simulated with known crosstalk combinations and subsequent analysis led to the identification of characteristics and impact of pathway interconnections. Our results revealed that the interconnections between the Snf1 and Snf3-Rgt2 pathway led to increased robustness in these signalling pathways. Overall, our approach contributes to the understanding of the function and importance of crosstalk in nutrient signalling.